1992
DOI: 10.1007/bf00008427
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton and zooplankton population dynamics and production of a recently formed African reservoir

Abstract: The study provides a 2 .5 year record of Rhenosterkop Dam (KwaNdebele, South Africa) plankton population dynamics and production in relation to physical and chemical changes which occurred during the trophic depression and stabilization phases of the reservoir . The mean volume of the reservoir was 4 % of full storage capacity . Water temperatures ranged from 14 ° C to 27 'C . Due to inorganic suspensoids, the euphotic zone averaged 2 .6 m . An anaerobic zone developed each summer . The nitrogen, soluble react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…Espíndola (1994) found four species of Notodiaptomus, namely Notodiaptomus iheringi, Notodiaptomus cearensis, Notodiaptomus conifer and Notodiaptomus nsp., during a two-year study of population dynamics of Copepoda Calanoida in Barra Bonita Reservoir. Looking back at samples collected in that 1982and 1984and Argyrodiaptomus furcatus in 1986, 1988, 1992and 1993, although in low densities. A new species of Notodiaptomus has appeared in Barra Bonita Reservoir since July 1992, starting in low numbers and progressively increasing throughout the year 1993 (Espíndola, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Espíndola (1994) found four species of Notodiaptomus, namely Notodiaptomus iheringi, Notodiaptomus cearensis, Notodiaptomus conifer and Notodiaptomus nsp., during a two-year study of population dynamics of Copepoda Calanoida in Barra Bonita Reservoir. Looking back at samples collected in that 1982and 1984and Argyrodiaptomus furcatus in 1986, 1988, 1992and 1993, although in low densities. A new species of Notodiaptomus has appeared in Barra Bonita Reservoir since July 1992, starting in low numbers and progressively increasing throughout the year 1993 (Espíndola, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…In Lake Rhenosterkop (South Africa), secondary production was recorded to vary from 8 to 14.8 gC.m , being greater than in the oligotrophic Lake Le Roux (Hart et al, 1983in Robarts et al, 1992, showing that eutrophic systems are more productive. Similarly, comparing the reservoirs of Barra Bonita, which is eutrophic, with the oligotrophic Lagoa Dourada Reservoir, both in Brazil, the production recorded in the present study was greater than that found in the latter.…”
Section: Discussionmentioning
confidence: 99%
“…The creation of a new reservoir and flooding of a lake may initiate a series of changes in the plankton community related to alterations in hydrology and nutrient availability that frequently result from inputs of large amounts of newly flooded terrestrial organic matter that may also stimulate bacterial activity (Paterson et al 1997). These effects almost always lead to the ecosystem evolving toward a new steady state of maturation with a trophic status generally lower than that observed immediately after flooding, and that may be achieved within years (Robarts et al 1992, Paterson et al 1997. It has been established over a broad range of aquatic systems that the number of active bacteria increases with the system's productivity (del Giogio & Scarborough 1995).…”
Section: Methodological Aspects and Quantitative Importance Of Ctc-pomentioning
confidence: 99%
“…Similar results were obtained for other reser voirs during the filling phase by Pinel-Alloul and l\llethot. (1984), Kimmcl et al (1988), Robarts et al (1992), who referred to this phenomenon as a 'trophic upsurge'. A significant increase of primar y production as a result of high nu trient conce ntrations during th e 'trophic upsurge' was also obser ved by tl1ese authors.…”
Section: Discussionmentioning
confidence: 99%
“…Email: zboavida@fc.ul.pt Accepted for publication 20 November 1998. ture (Pinel-Alloul & Methot 1984) and on both phytoplankton and zooplankton dynamics (Robarts et al 1992) as well as on organic matter production and decomposition (Kimmel et al 1988) .…”
Section: Introductionmentioning
confidence: 99%